Frequency of Routine Testing for Coronavirus Disease 2019 (COVID-19) in High-risk Healthcare Environments to Reduce Outbreaks. (26th October 2020) - Chin, Elizabeth T; Huynh, Benjamin Q; Chapman, Lloyd A C; Murrill, Matthew; Basu, Sanjay; Lo, Nathan C
Abstract: Routine asymptomatic testing strategies for COVID-19 have been proposed to prevent outbreaks in high-risk healthcare environments. We used simulation modeling to evaluate the optimal frequency of viral testing. We found that routine testing substantially reduces risk of outbreaks, but may need to be as frequent as twice weekly.